Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 22. Beitrag: Homoptera: Auchenorrhyncha. - Dlabola, Jiří (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The above paper on the Cicadas of Albania deals with the results of the expedition of the Deutsches Entomologisches Institut 1961, including a small number of specimens collected in this country by some entomologists of DDR and CSSR in 1958/1959, as like as the respective literature. The material of the expedition contained 1064 specimens belonging to 110 species (61 of which are new to Albania). A new species (Macropsidius friesei n. sp.) is described and figured. 3 more species new to Albania were found among material collected by Moucha and Klausnitzer. Including some records, which remained still dubious, there are now 156 species of this group known from Albania. Nomenclatural Acts friesei Dlabola, 1964 (Macropsidius), spec. n.